A study on knowledge, attitude and practice on colorectal cancer screening among average risk malay patients attending selising health clinic - Ibrahim, Idora (2011)
INTRODUCTION: Colorectal cancer is rapidly increasing in Asia. Despite the rising trend in incidence and mortality, colorectal cancer screening rates are still low in most Asian countries. The acceptability of CRC screening is influenced by people’s knowledge and attitude. This study was conducted to evaluate the knowledge, attitude and practice of Malay people toward CRC screening.